The modern‐day Odysseus: How mental health providers can better reintegrate modern warriors and mitigate suicide risk. Issue 5 (17th January 2020) - Geraci, Joseph; Murray, Christopher; Kapil‐Pair, K. Nidhi; Herrera, Shaynna; Sokol, Yosef; Cary, Julianne; Landa, Yulia; Goodman, Marianne
Abstract: During their return from combat, warriors from Greek mythology and Native American traditions received the support of "helpers" to guide the reintegration back into their communities or tribes. While the military provides our modern warriors (MWs), similar helpers, during their departure from their hometown and during their initiation into the military, there is a dearth of comparable help when MWs reintegrate back into their hometowns. We strive to assist mental health providers to serve as such helpers for MWs to shape their reintegration environment, enable MWs to meet their unique needs after exiting the military, ameliorate the MW suicide epidemic, and facilitate MWs to continue their next "mission" to serve and improve society with a newly forged MW identity, wisdom, and sense of purpose.